O ensino do vocabulário nas aulas de Língua Portuguesa: da realidade a um modelo didático - Dargel, Ana Paula Tribesse Patrício [UNESP] (2011)
The lexicon is the level of the language that shows the most the knowledge one has about the world, since the lexical unities refer to elements (actions, objects, feelings, qualities, events) of the human life universe. The fulfilment of this work was motivated by the perception of the importance that the lexical expansion has during someone's journey. From this point of view, it's a fact that the school has an important role on the lexical development of a student because it's the place where he/she is in contact with a great variety of texts. Thereby, this thesis emphasized the aspects related to vocabulary teaching and shows a methodological, theoretical and practical subsidy for the Basic Education Portuguese teacher by means of: i) theoretical orientations about vocabulary teaching; ii) suggestions on how to teach a student to know and like a dictionary and, this way, to contribute that this student will use the dictionary as a useful, important and pleasurable didactic resource, while reading and writing; iii) several exercises on vocabulary with some orientations about how the student can use the dictionary. From this perspective, the objective traced to develop this work was: i) to produce a methodology of teaching based on the aspects of the lexicon pedagogy during the Portuguese classes of the Basic Education, precisely in the groups of 5th and 8th grades. In this work, in the item where the exercises on vocabulary are presented, a database was organized in the Program Folio Views 4.2 with the texts extracted from the books used in the Portuguese classes of public schools in the city of Cassilândia - Mato Grosso do Sul.